2023
DOI: 10.3390/ijms24087087
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion to the Brain Endothelium Selects Breast Cancer Cells with Brain Metastasis Potential

Abstract: Tumor cells metastasize from a primary lesion to distant organs mainly through hematogenous dissemination, in which tumor cell re-adhesion to the endothelium is essential before extravasating into the target site. We thus hypothesize that tumor cells with the ability to adhere to the endothelium of a specific organ exhibit enhanced metastatic tropism to this target organ. This study tested this hypothesis and developed an in vitro model to mimic the adhesion between tumor cells and brain endothelium under flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The initial step of brain metastasis includes CTCs arresting within the lumen of brain microvessels [ 117 ]. A small microvascular lumen size [ 117 ] and the interaction of cell adhesion molecules (CAMs) on the surface of CTCs with corresponding CAMs on brain ECs [ 118 ] are considered to contribute to this CTC arrest. In particular, BC cells expressing high levels of MUC1 , VCAM1 , and VLA-4 were able to strongly adhere to brain endothelium and withstand fluid shear stress normally occurring within blood vessels [ 118 ].…”
Section: Soil: Tissue-specific Properties At Metastatic Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial step of brain metastasis includes CTCs arresting within the lumen of brain microvessels [ 117 ]. A small microvascular lumen size [ 117 ] and the interaction of cell adhesion molecules (CAMs) on the surface of CTCs with corresponding CAMs on brain ECs [ 118 ] are considered to contribute to this CTC arrest. In particular, BC cells expressing high levels of MUC1 , VCAM1 , and VLA-4 were able to strongly adhere to brain endothelium and withstand fluid shear stress normally occurring within blood vessels [ 118 ].…”
Section: Soil: Tissue-specific Properties At Metastatic Sitesmentioning
confidence: 99%
“…A small microvascular lumen size [ 117 ] and the interaction of cell adhesion molecules (CAMs) on the surface of CTCs with corresponding CAMs on brain ECs [ 118 ] are considered to contribute to this CTC arrest. In particular, BC cells expressing high levels of MUC1 , VCAM1 , and VLA-4 were able to strongly adhere to brain endothelium and withstand fluid shear stress normally occurring within blood vessels [ 118 ]. In addition, breast CTCs induced the expression of E-selectin, VCAM-1, ALCAM, ICAM-1, VLA-4, and β 4 integrin by brain ECs, demonstrating the reciprocal nature of these adherence mechanisms [ 119 ].…”
Section: Soil: Tissue-specific Properties At Metastatic Sitesmentioning
confidence: 99%
“…The authors also highlighted the importance of other NVU cell types, such as astrocytes for BBB integrity, but also their prohibitive role in cancer metastasis. A recent study by Zhang et al [ 302 ] suggested the enhanced adhesion of circulating breast cancer cells with metastasis potential to the brain endothelium. The microfluidic model included varying shear stress, selecting those cells with the highest adhesion to BMECs.…”
Section: Disease-specific Modeling Of Neuroinflammationmentioning
confidence: 99%
“…In addition to its effects on cancer and stromal cells, oxidative stress can modulate endothelial cell function, which is suggested by research on the OGG1-NFκB interaction in chromatin [ 62 ]. Dysfunction of the vascular endothelial barrier in cancer has been implicated in disease pathology, progression, and outcome [ 6 , 130 ], as vascular endothelial cells have a key role during tumor metastasis [ 131 ], and the interaction between cancer cell and endothelium has been documented in research models for migration through the blood–brain barrier [ 132 ]. In particular, endothelial–mesenchymal transition has been proposed to occur after anthracycline treatment and to initiate vascular remodeling [ 133 ]; anthracyclines are known triggers of NFκB activation [ 134 ] and specifically initiate endothelial-to-mesenchymal transition [ 135 ] on the one hand, and on the other hand, NFκB activation protects cancer cells from apoptosis [ 136 ].…”
Section: Phenotypic Transitions In the Microenvironmentmentioning
confidence: 99%